ISLAMIC AND POSITIVE LAW PERSPECTIVES OF GRATIFICATION IN INDONESIA - Fazzan Fazzan; Abdul Karim Ali (Islam Futura, 2015)
A set of rules about gratification is a novelty within society and perceived to collide with the cultural of giving in the Islamic society in Indonesia. This study is aimed to explore the meaning of gratification from the perspective of positive law in Indonesia, and the boundaries of gratification, which is interdicted by the laws. This study used the normative method which analyzes the positive law in Indonesia regulating the gratification. The result of this study shows that gratification in the positive law and Islamic law perspective has a wide meaning including each tribute for Civil Servant or State Apparatus. According to Indonesia law, gratification could be either positive or negative. Gratification which is allowed by the laws is a gift with a pure tension of the recipient to the Civil Servant or State Apparatus without expecting to achieve anything in return. In contrary, gratification which is not allowed by the laws is a gift for the Civil Servant or State Apparatus because of their position in that employment and the purpose of it is not related to their duty or order. Based on Islamic law perspective, gratification is forbidden by nas al-Qur’an and hadith. Substantially, the rule of positive law in Indonesia which forbids the gratification practices has fit with the aim of Islamic law. In positive law in Indonesia, however, there is still gratification allowed that leads to the fraudulence. Instead, in Islamic law all kinds of gratifications for the State Apparatus and the Civil Servant are forbidden in order to ensure all the ways of fraudulences are closed off.